If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 4 + -1(3x) Remove parenthesis around (3x) 21 = 4 + -1 * 3x Multiply -1 * 3 21 = 4 + -3x Solving 21 = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 21 + 3x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 21 + 3x = 4 + 0 21 + 3x = 4 Add '-21' to each side of the equation. 21 + -21 + 3x = 4 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 4 + -21 3x = 4 + -21 Combine like terms: 4 + -21 = -17 3x = -17 Divide each side by '3'. x = -5.666666667 Simplifying x = -5.666666667
| 6a+15=69 | | 3x+5=3x-10 | | -3(t+2)=6 | | 8n-42=5n | | 3x-2(4x-3)=2-3(x-1) | | -4x+7=5x+10 | | -15(t^2+120t+10)= | | 6x=x+35 | | 2x^2-5=-55 | | 2d*17=25 | | 9(w-2)=63 | | 5+8x=26+x | | 3d+17=24.5 | | 25-n=n-3 | | 4(-7x+2)+2x=-2 | | 4x+20=5x+15 | | -8-5(7x+1)=-1 | | 9x+4(-3x-4)=-14-5x | | 0.5x*(6x^2+3x-1)=4 | | 6(5x-3)-3x-2=5 | | 4x+2=-x-3 | | 5x-2(4-x)=20 | | 0.5x*(12x^3+6x^2-2x)=4 | | 4(-2x+5)=-6 | | X+2=4x+5 | | x^2+18x+77=0 | | -6x-6=18 | | 4(x+18)=788 | | 9x-3(2x-4)=15 | | 5x-13-3x-19=-6 | | -8=-17+0-14 | | 5x-13-3c-19=-6 |